THE DESIGN OF WEB-BASED INFORMATION SYSTEM OF BATIK INDONESIA - Hamdi, Agus (Bina Nusantara University, 2012)
While the Government is heavily promoting batik abroad, it turned out the conditions within the country is not much supportive. Many of the younger generation are not interested in acquiring the art of batik since batik artisans are still largely dominated by the old. Not to mention the problem of the patent of a few motifs that turns out to have been intercepted by Malaysia. Seeing the dark future of this batik, it needs an effort to preserve the traditional batik by not to be drown in the flood of modern life that lacks of appreciation of traditional batik. In anticipating of that, Indonesian batik needs web information that supports and provides satisfactory service for the visitors of the website.Keywords: Batik Information, website